The Influence of Work-life balance, Mindfulness, and Work engagement on Employee Performance in Bali with Gender as a Moderating - Ni Putu Mirah Suandewi; Putu Irma Yunita (SENTRI: Jurnal Riset Ilmiah, 2026)
This study examines the influence of Work–life balance, Mindfulness, and Work engagement on employee performance, as well as the moderating role of gender within these relationships. The research was conducted in the Province of Bali, where service-based industries demand high adaptability and consistent productivity from employees. Using a quantitative design, data were collected from 160 respondents through an online structured questionnaire. The analysis employed Hierarchical Regression Analysis (HRA) with SPSS to test both the direct and moderating effects. The results show that Work–life balance, Mindfulness, and Work engagement each have a significant positive impact on employee Performance, highlighting the importance of psychological readiness and personal well-being in supporting optimal Work outcomes. Gender does not directly affect performance and does not moderate the influence of Work–life balance or Mindfulness. However, Gender significantly moderates the relationship between Work engagement and Performance, indicating that the strength of engagement’s effect varies across gender groups. These findings emphasize the need for organizations to strengthen employee resources, cultivate mindful work practices, and enhance engagement to improve performance in dynamic service environments.